Juvenile Myasthenia and Puberty - J Gordon Millichap (Pediatric Neurology Briefs)
The influence of race, sex, and puberty on incidence, severity, and outcome of juvenile myasthenia gravis beginning before age 20 years was evaluated in 115 patients seen at the University of Virginia, Duke University, and University of North Carolina at Chapel Hill.